Living the good life with autism - Schneider, Edgar, 1932- (Jessica Kingsley Publishers, 2003)
His discovery only in retirement that he has high-functioning autism provided Edgar Schneider at last with an explanation for his many differences, explored in Discovering my Autism. In this book he takes up the story, telling of his marriage to a like-minded woman, and of the day-to-day realities of life with this condition. His description of autistic attitudes towards relationships, politics, theology and health are rich and original. Schneider argues that if people with high-functioning autism and Asperger Syndrome are left to their own devices they are capable of making lives for themselves.